Reaction of Nitrilimines with Aromatic and Heterocyclic Ketoximes, Part 3: Synthesis of Substituted 1,2,4-Triazoles and 1,2,4,8-Tetraazaspiro[4,5]dec-2-enes - S. Ferwanah, Abdel-Rahman; M. Awadallah, Adel; A. Khafaja, Naveen (Asian Journal of Chemistry, 2010)
Nitrilimines (2a-g) react with acetophenone oxime (3) to afford 3-acyl-1- aryl-4,5-dihydro-5-methyl-5-phenyl-1H-1 ,2,4-triazoles (4a-g). Similarly, the reaction of nitrilimines (2) with 1-methyl-4-piperidone oxime (6) gives 3-acyl-1-aryl-8-methyl-1,2,4,8-tetraazaspiro[ 4,5]dec-2-enes (7). Spectral data of the title compounds are discussed.